2018
DOI: 10.1021/acs.iecr.8b02421
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical ZSM-5 Zeolites with Tunable Sizes of Building Blocks for Efficient Catalytic Cracking of i-Butane

Abstract: Hierarchical ZSM-5 zeolites have been receiving increasing attention from both fundamental research and industrial applications. From the chemical engineering viewpoint, the introduction of building block of ZSM-5 could give consideration to both external surface acidities and diffusion properties which are important in parallel sequence reaction for the final product distribution. In this work, hierarchical ZSM-5 with different sizes of building blocks were successfully prepared by tuning the water/silica rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…[70] To verify this perspective, the effect of different Brønsted acid density related to using different LDH loading in the composite on the catalytic performance was further studied. Interestingly, the composites with the highest and lowest LDH content (ZSM-5@MgAlO x (38) and ZSM-5@MgA-lO x (19), respectively) exhibit a significantly lower light olefins yield compared with the one with moderate LDH content (ZSM-5@MgAlO x (33)). The highest LDH loaded catalyst also relates to a lack of Brønsted acid sites, and therefore there are a few available active sites for catalytic cracking.…”
Section: Catalytic Performance In N-pentane Crackingmentioning
confidence: 96%
See 2 more Smart Citations
“…[70] To verify this perspective, the effect of different Brønsted acid density related to using different LDH loading in the composite on the catalytic performance was further studied. Interestingly, the composites with the highest and lowest LDH content (ZSM-5@MgAlO x (38) and ZSM-5@MgA-lO x (19), respectively) exhibit a significantly lower light olefins yield compared with the one with moderate LDH content (ZSM-5@MgAlO x (33)). The highest LDH loaded catalyst also relates to a lack of Brønsted acid sites, and therefore there are a few available active sites for catalytic cracking.…”
Section: Catalytic Performance In N-pentane Crackingmentioning
confidence: 96%
“…To overcome these drawbacks, zeolite catalysts have been modified by several approaches, for example, the creation of the additional mesoporosity in zeolite frameworks [12,13,14,15] as well as the modification with rare earth and metals, such as metal oxides and alkaline-earth metals. [16,17,18,19] However, there is the limitation of an excessive number of strong Brønsted acid sites on external surfaces of zeolites, leading to competing hydride transfers and further side reactions, such as oligomerization, isomerization, cyclization, and aromatization. [20,21] To deal with these issues, the modification of external acidity of zeolites has been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al demonstrated that the conversion and selectivity of isobutane cracking may be tuned through controlling the mesoporosity of ZSM-5 catalysts. More mesoporous samples demonstrated higher conversion and selectivities due to an improved diffusion, as well as improved catalyst stabilities and lifetimes [91]. The introduction of mesoporosity has also been found to improve resistance to coking, much like when comparing channel versus cage topologies.…”
Section: Influence Of Mesoporosity In Zeolitesmentioning
confidence: 98%
“…The catalytic conversion of methanol over acidic zeolite has become an eminent route to produce hydrocarbon products, such as olefins, gasoline, and aromatics. , ZSM-5 is a representative catalyst for the abovementioned reactions attributed to its plentiful active sites and shape-selective pore structure (0.53 nm × 0.51 nm sinusoidal channels and 0.56 nm × 0.53 nm straight channels). , However, such typical micropores cause space limitation for the diffusion of bulky product molecules. These molecules would be trapped in the channels and undergo condensation, hydrogen transfer, and elimination reactions to form coke precursors. , The coke precursors finally convert into coke and deposit in micropores, cover the active sites, and block zeolite channels, resulting in catalyst deactivation. , Especially for the ZSM-5 with a low Si/Al ratio, the high acid density and strong acid strength promote the coke formation, leading to a fast catalyst deactivation. , Therefore, optimization of pore structure and surface acidity should be considered to improve catalytic stability. , …”
Section: Introductionmentioning
confidence: 99%